Towards A Pan–Cultural Personality Structure: Input from 11 Psycholexical Studies. Issue 5 (September 2014) - De Raad, Boele; Barelds, Dick P. H.; Timmerman, Marieke E.; De Roover, Kim; Mlačić, Boris; Church, A. Timothy
The purpose of the present study is to find the common kernel of different trait taxonomic studies and find out how the individual structures relate to this common kernel. Trait terms from 11 psycholexically based taxonomies were all translated into English. On the basis of the commonalities in English, the 11 matrices were merged into a joint matrix with 7104 subjects and 1993 trait terms. Untranslatable terms produced large areas with missing data. To arrive at the kernel structure of the joint matrix, a simultaneous component analysis was applied. In addition, the kernel structures were compared with the individual taxonomy trait structures, obtained via principal component analysis. The findings provide evidence of a structure consisting of three components to stand out as the core of the taxonomies included in this study; those components were named dynamism, affiliation, and order. Moreover, the relations between these three kernel components and those of a six–component solution (completing the six–factor model) are provided. Copyright © 2014 European Association of Personality Psychology